2006 IEEE 4th World Conference on Photovoltaic Energy Conference 2006
DOI: 10.1109/wcpec.2006.279598
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Rear Surface Passivation for Industrial Multicrystalline Silicon Solar Cells

Abstract: Thermal oxides are commonly used for the production of high-efficiency silicon solar cells from mono-and multicrystalline silicon and have led to the highest conversion efficiencies reported so far. Following the development of high-efficiency cells of small area (1 or 4 cm 2 ) using photolithographic techniques, in the present study large area cells (³100 cm 2 ) are manufactured employing an industrial front structure. In this paper we present two different passivation schemes for the rear surface of industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…80% achieved on large area multicrystalline silicon solar cells in a different study. 15 The average efficiencies for all materials were about 18%, close to 20%, were measured for small area cells of 1 cm 2 , independent of doping type or concentration. The 19Á8% efficiency for the 4 cm 2 cell made from ScanWafer material represents the highest value for a multicrystalline silicon solar cell of this size.…”
Section: Solar Cell Resultssupporting
confidence: 56%
“…80% achieved on large area multicrystalline silicon solar cells in a different study. 15 The average efficiencies for all materials were about 18%, close to 20%, were measured for small area cells of 1 cm 2 , independent of doping type or concentration. The 19Á8% efficiency for the 4 cm 2 cell made from ScanWafer material represents the highest value for a multicrystalline silicon solar cell of this size.…”
Section: Solar Cell Resultssupporting
confidence: 56%
“…In particular, laser ablation processes are required in monolithic interconnection of thin film photovoltaic modules 1,2. Moreover, it has been demonstrated that processes involving lasers as a crucial tool, such as laser grooved buried front contact (LGBC)3 and laser fired contact (LFC)4 improve efficiencies for crystalline silicon photovoltaic devices. Consequently, research in laser processing of the materials used in the photovoltaic industry has become a highly attractive field, especially since laser technology developments have the potential to further improve the performance of photovoltaic devices 5…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor technology or microelectronics including solar cells has been adopted to form micro- or nano-sized state-of-the-art structures which can reduce system size, improve its performance, achieve lower system cost, and so on [1-3]. Generally, a semiconductor structure or system is manufactured by a combination of additive (film deposition) and subtractive (etching) processes.…”
Section: Introductionmentioning
confidence: 99%